Beitrag zur Kenntnis der Tineiden von Iran und Pakistan (Lepidoptera: Tineidae). - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1971)
In addition to formerly published contributions to the Tineid moths fauna of Iran and Pakistan there are mentioned new records of 16 species three of which are described as new. Nomenclatural Actsquettaella Petersen, 1971 (Infurcitinea), spec. n.teheranensis Petersen, 1971 (Infurcitinea), spec. n.kasyi Petersen, 1971 (Obesoceras), spec. n.libanoticum Petersen, 1968 (Obesoceras), syn. n. of Obesoceras holtzi (Rebel, 1902)